Detecting the Black Hole Candidate Population in M51’s Young Massive Star Clusters: Constraints on Accreting Intermediate-mass Black Holes - Kristen C. Dage; Evangelia Tremou; Bolivia Cuevas Otahola; Eric W. Koch; Kwangmin Oh; Richard M. Plotkin; Vivian L. Tang; Muhammad Ridha Aldhalemi; Zainab Bustani; Mariam Ismail Fawaz; Hans J. Harff; Amna Khalyleh; et al. (The Astrophysical Journal)
Intermediate-mass black holes (10 ^2  <  M _BH  < 10 ^5 M _⊙ ) are an open question in our understanding of black hole evolution and growth. They have long been linked to dense star cluster environments, thanks to cluster dynamics, but there are a limited number of secure detections. We leverage existing X-ray observations from the Chandra X-ray Observatory and optical catalogs from the Hubble Space Telescope (HST) as well as new radio observations from the Karl G. Jansky Very Large Array to search for any evidence of accreting black holes in young massive star clusters in the nearby galaxy M51. We find that of 44 bright ( L _X  > 10 ^38 erg s ^−1 ) X-ray point sources in M51, 24 had probable matches to objects including possible associated star clusters in the HST Legacy Extragalactic UV Survey catalog, seven of which were classified as contaminants (background galaxies or foreground stars). We explore the optical properties of the remaining 17 sources, including cluster age and mass estimates, and search for radio counterparts in the 8–12 GHz band. The lack of radio counterparts to X-ray sources we know to be associated with young massive star clusters in M51 suggests that we do not significantly detect hard-state intermediate-mass black holes (IMBHs)  ~10 ^4 M _⊙   or above. However, more sensitive radio facilities, like the Square Kilometre Array and next-generation Very Large Array, may be able to provide evidence for IMBHs with masses down to  ~10 ^3 M _⊙ .